A Year in the Life of a Contaminated Heater-Cooler Unit With Mycobacterium chimaera?. (5th May 2017) - Garvey, Mark I.; Bradley, Craig W.; Walker, Jimmy
Abstract : OBJECTIVE: Heater-cooler units (HCUs) have been shown to be a source of Mycobacterium chimaera infections. For the past year, weekly water samples have been taken from HCUs used at University Hospitals Birmingham (UHB) NHS Foundation Trust. We report the microbial contamination of the HCUs over a year detailing the decontamination regimes applied at UHB to reduce the microbial load. DESIGN: Observational study SETTING: UHB is a tertiary referral teaching hospital in Birmingham, United Kingdom, that provides clinical services to nearly 1 million patients every year. The UHB Cardiac department is one of the largest in the United Kingdom and provides treatment for adult patients with a wide range of cardiac diseases. METHODS: Water samples taken from HCUs used at UHB for cardiopulmonary bypass surgery were sampled over a year to determine the number of microorganisms by membrane filtration. Various decontamination processes were employed throughout the year. RESULTS: Varying total viable counts containing a wide variety of microorganisms were obtained from water inside the HCUs. No M. chimaera were isolated after replacement of the HCU internal tubing. Stringent decontamination regimes resulted in degradation of the HCUs and increased TVCs after several months. CONCLUSION: More work is required to ensure effective decontamination processes to reduce the microbial load within the HCUs. Our studies indicate that weekly water sampling for TVC will be required indefinitely to monitor the water quality in these units as well as regular replacement of the tubing to control the build-up of biofilm. Infect Control Hosp Epidemiol 2017;38:705–711